On the Pyroelectric and Triboelectric Phenomena in Ferrofluids. Issue 10 (13th May 2022) - Garofalo, Erik; Bevione, Matteo; Cecchini, Luca; Chiolerio, Alessandro
Abstract: Owing to the waste of energy originated by any physical or chemical process, approaches for reducing the energy losses have been conceived and, nowadays, energy recovery and conversion systems represent a worldwide‐recognized solution. The advent of colloidal‐based cybernetic systems highlights the essential role of energy harvesting, storage, and management capabilities coped by colloidal energetic systems. In this work, an alternative to thermoelectricity generation is demonstrated by means of a magnetic colloid based on Fe3 O4 nanoparticles (NPs). The ferrofluid (FF) tribo‐ and pyroelectric features are explored in order to increase the amount of harvested energy. The findings suggest that the FF shows both triboelectric and pyroelectric charge displacement. A capacitive electrode is more efficient for accumulating potentials up to 48 V developed by triboelectricity while a resistive one is essential to collect pyroelectric charges up to 22 nA, which helped to estimate the FF pyroelectric coefficient, reaching the remarkable value of 25.2 μ Cm −2 K −1 . A simplified equivalent model of the inductive setup is proposed, suggesting that increasing the fluid temperature a reduction of FF inductance due to demagnetization effects occurs. Abstract : This article investigates the energy harvesting capability of an oil‐based ferrofluid (FF) for application in liquid‐state robotic systems. Asides electromagnetic induction, pyroelectric and triboelectric phenomena are analyzed, appearing when the colloid is heated and flows along a pipe. Characterization of open circuit voltage and short circuit current suggests that FF shows both triboelectricity and pyroelectricity with promising performances.